2018
DOI: 10.1124/mol.118.113647
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz and Efavirenz-like Compounds Activate Human, Murine, and Macaque Hepatic IRE1α-XBP1

Abstract: Efavirenz (EFV), a widely used antiretroviral drug, is associated with idiosyncratic hepatotoxicity and dyslipidemia. Here we demonstrate that EFV stimulates the activation in primary hepatocytes of key cell stress regulators: inositol-requiring 1a (IRE1a) and X-box binding protein 1 (XBP1). Following EFV exposure, XBP1 splicing (indicating activation) was increased 35.7-fold in primary human hepatocytes. In parallel, XBP1 splicing and IRE1a phosphorylation (p-IRE1a, active IRE1a) were elevated 36.4-fold and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Primary hepatocytes were stained and imaged, and those images were processed as previously described. 56 …”
Section: Methodsmentioning
confidence: 99%
“…Primary hepatocytes were stained and imaged, and those images were processed as previously described. 56 …”
Section: Methodsmentioning
confidence: 99%
“…JNKs are a family of serine/threonine kinases that are important regulators of cellular responses to stress, including cell death. There is also evidence that points to the capacity of EFV to induce ER stress and unfolded protein response (UPR) in human hepatic cells [ 98 , 99 ]. It activates key ER stress/UPR controllers, inositol-requiring 1α (IRE1α) and X-box binding protein 1 (XBP1) through increased formation of ROS, and this effect is thought to contribute to EFV-mediated hepatocyte death [ 99 ].…”
Section: Mechanisms Of Nnrti-induced Liver Injurymentioning
confidence: 99%
“…There is also evidence that points to the capacity of EFV to induce ER stress and unfolded protein response (UPR) in human hepatic cells [ 98 , 99 ]. It activates key ER stress/UPR controllers, inositol-requiring 1α (IRE1α) and X-box binding protein 1 (XBP1) through increased formation of ROS, and this effect is thought to contribute to EFV-mediated hepatocyte death [ 99 ]. Our research shows that, concomitantly with mitochondrial dysfunction and ER stress, EFV-exposed cells display altered autophagy [ 100 ].…”
Section: Mechanisms Of Nnrti-induced Liver Injurymentioning
confidence: 99%
“…JNKs are a family of serine/threonine kinases that are important regulators of cellular responses to stress, including modulation of cell death. A recent study by the same group demonstrated that EFV and several EFV-like compounds activate key cell stress controllers such as inositol-requiring 1α (IRE1α) and X-box binding protein 1 (XBP1), a regulator of the mammalian UPR [ 89 ]. The molecular mechanism by which EFV activated IRE1α and, subsequently, IRE1α-catalyzed splicing of XBP1 mRNA involved increased formation of ROS, an event that can lead to activation of the ER stress response, including the IRE1α-XBP1 signaling axis, whose activation was demonstrated in humans, mice, and macaques.…”
Section: Cart-related Apoptosis In Hepatocytesmentioning
confidence: 99%
“…The molecular mechanism by which EFV activated IRE1α and, subsequently, IRE1α-catalyzed splicing of XBP1 mRNA involved increased formation of ROS, an event that can lead to activation of the ER stress response, including the IRE1α-XBP1 signaling axis, whose activation was demonstrated in humans, mice, and macaques. Thus, activation of the IRE1α-XBP1 axis is thought to contribute to EFV-mediated hepatocyte death [ 89 ] ( Figure 2 ). In another investigation, this NNRTI was used as a model of drug-induced inhibition of complex I in primary mouse hepatocytes, and the authors concluded that this effect was the cause of cytotoxicity, as inhibition of complex I resulted in increased oxidative stress via the formation of peroxynitrite, which can trigger mitochondria-mediated cell death [ 90 ].…”
Section: Cart-related Apoptosis In Hepatocytesmentioning
confidence: 99%